Tawang Volleyball Cup sebagai Ajang Pemersatu Masyarakat Desa Tawang - Nurfaizzatu Dzikrillah; Eliza Mutiara Nasywa; Martin Sudarmono (Jurnal Bina Desa, 2026)
Tawang Volleyball Cup is an initiative by Giat 9 Students of Universitas Negeri Semarang aimed at strengthening social bonds and enhancing the sense of togetherness among the residents of Tawang Village through an inter-neighbourhood volleyball tournament. This event not only improves the technical and mental abilities of the players, but also applies the values of Pancasila, especially the third principle "The Unity of Indonesia". In addition, this tournament coincides with the celebration of the 79th Anniversary of the Republic of Indonesia, increasing the spirit of nationalism and togetherness. Through active participation, the community strengthens their sense of togetherness, expands social networks, and develops their sports skills, so that the end result is expected that the Tawang Volleyball Cup will be an effective unifying event and setting Tawang Village as an example for other villages in building harmonious and competitive community.